Pengaruh Parameter Faktor Stir Casting pada Porositas KOmposit Al-SiC - Sadi, Sadi; Malau, Viktor; Wildan, M Waziz; Suyitno, Suyitno (ROTOR, 2014)
This research aims to analyze the effect of stir casting factor parameters on Al-SiC composite porosity using Taguchi method. Composite materials used aluminum alloy Al-Si as matrix and SiC particle (silicon carbide) sized -400 mesh as reinforcement. Al-SiC composites specimen porosity was tested using Archimedes principles. Experimental design using L16 orthogonal arrays Taguchi method standard. Factors used for the experiment were SiC content, melt temperature, rotation speed and stirring time duration, each using 4 variation. Experimental results showed that increasing SiC content parameters and stirring rotation speed from 100 into 300 rpm can increase Al-SiC composite oporosity, but increasing melt temperature above 700 C and stirring time from 10-30 minutes candecrease the porosity. The most significant factor affecting Al-SiC composite porosity was SiC conten with 84,7 % contribution. Microstructures of Al-SiC casting composites were observed using scanning electron microscopy (SEM). Keywords: Al-SiC composites, porosity, stir casting, experimental design, taguchi method